John Bascom and the origins of the Wisconsin Idea - Hoeveler, J. David, 1943- (The University of Wisconsin Press, 2016)
In the Progressive Era of American history, the state of Wisconsin gained national attention for its innovative economic and political reforms. Amidst this ferment, the ""Wisconsin Idea"" was popularized-the idea that a public university should improve the lives of people beyond the borders of its campus. During his term as governor (1901-1906), Robert La Follette routinely consulted with University of Wisconsin researchers to devise groundbreaking programs and legislation. Although the Wisconsin Idea is often attributed to a 1904 speech by Charles Van Hise, then president of the University of
Keywords: Bascom, John, -- 1827-1911.; University of Wisconsin -- Presidents -- Biography.; University of Wisconsin -- History.; Bascom, John, -- 1827-1911; University of Wisconsin; Progressivism (United States politics); College presidents -- Wisconsin -- Biography.; Community and college -- Wisconsin -- History.; Social gospel -- Wisconsin.; Wisconsin -- Politics and government -- 1848-1950.; Progressisme -- États-Unis.; Présidents et recteurs d'université -- Wisconsin -- Biographies.; Relations université-collectivité -- Wisconsin -- Histoire.; Évangile social -- Wisconsin.; Wisconsin -- Politique et gouvernement -- 1848-1950.; BIOGRAPHY & AUTOBIOGRAPHY -- Educators.; EDUCATION -- Higher.; College presidents; Community and college; Politics and government; Presidents; Social gospel; Wisconsin; 1848-1950; collective biographies.; Biographies; History; Biographies.